A FUTURE APPROACH FOR HUMAN FACE IDENTIFICATION (International Journal of Engineering and Computer Science, 2013)
Human Face Identification is an Information technology that identifies the positions of human faces in bits of images. It recognizes Human facial properties and eliminates everything else, such as animals, cars and bodies. It plays an important role in video surveillance, smart cards, protection, Face Databases, Access control and Human Computer Identification. Human face is one of the most significant features to detect persons in an image. As sufficient luminous information is not available in the existing approach, we propose a new method to identify various colors of human face. The proposed methodology identifies how to reveal human face from the background image.